WOMEN’S ACCESS TO EDUCATION IN PAKISTAN - Tuxtasinova Shaxnoza Ibrohimovna (Bright Mind Publishing, 2026)
This article analyzes women’s access to education in Pakistan through historical, social, and political perspectives. The study examines state policies in the field of women’s education from the period of Pakistan’s independence onward, the impact of democratization processes on the education system, and reforms aimed at ensuring gender equality. In addition, regional and social disparities in women’s education, patriarchal values, economic constraints, and the weakness of law enforcement institutions are identified as major obstacles. The article also highlights the role of civil society and international organizations in promoting and developing women’s education in Pakistan.
Keywords: Pakistan, women’s education, gender equality, democratization, social development, civil society, education policy.